Klasse-E Leistungsverstärker mit Lastmodulation - Lautenbacher, Thomas; Schmidt, Christian; Fehr, Matthias; Kamper, Michael; Weigel, Robert; Fischer, Georg; Kölpin, Alexander (EEEfCOM 2012, 2012)
elib2cris::1512001600,lautenbacher2012a

Wireless Production Tools - PMSE - Radio Spectrum Scanning at the Brazilian 2018 FIA Formula OneWorld Championchip - Fehr, Matthias; Minami, Mario; Filgueiras, Felipe; Seeger, Pia; Fontoura Ponchet, Andre; Fischer, Georg (SET International Journal of Broadcast Engineering, 2020)
Major international sporting competitions such as Formula 1 GP Championship offer a great opportunity to check the use of the frequency spectrum in many respects, such as operation, regulation, equipment, demands and conflicts between all involved professionals, content producers, technical support and local regulatory agencies. In this piece of work, spectral scanning recordings were performed in the range of 410 to 870 MHz, covering wireless PMSE microphones at the 2018 F1 GP Brazil. The spectral scanning equipment was installed at two different locations, the international technical area for the TV stations (compound) with the UFABC semi-portable 6 GHz R&S spectrum analyzer and the TV Globo booth with APWPT’s semi-portable 3 GHz R&S spectrum analyzer in the middle of the pit line. There was a distance of about 2 km between the two locations. The equipment, controlled by specialized software. The radio spectrum was in use both by the technical team and the TV content production teams themselves, as well as the production, transmission and communication content between the various teams and their car drivers and a crew in a helicopter equipped with video cameras. In the three official days of the event from November 9th Friday to 11th Sunday, during many practice laps of the Interlagos racetrack, the official classification laps and the F1 GP Race itself, many links of audio PMSE equipment were recorded, the essential data of which were continuously monitored. Finally, the spectrum recordings were compared with TV Globe's coordination information. This reduced errors in the evaluation of the spectrum recording. Using previous reports since 2014 we can compare the number of microphones used in the Brazilian F1 GP and contrast with analogous recording procedures in Italian F1 GP at the same period.<br
Keywords: PMSE; Spectrum Scan; Occupation receiver